2018
DOI: 10.1186/s12985-018-0955-1
|View full text |Cite
|
Sign up to set email alerts
|

Engineering T7 bacteriophage as a potential DNA vaccine targeting delivery vector

Abstract: BackgroundDNA delivery with bacteriophage by surface-displayed mammalian cell penetrating peptides has been reported. Although, various phages have been used to facilitate DNA transfer by surface displaying the protein transduction domain of human immunodeficiency virus type 1 Tat protein (Tat peptide), no similar study has been conducted using T7 phage.MethodsIn this study, we engineeredT7 phage as a DNA targeting delivery vector to facilitate cellular internalization. We constructed recombinant T7 phages tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…is observation provides valuable information on the pharmacokinetic aspects of bacteriophage treatment, which is vital in the context of using bacteriophages as an alternative antimicrobial therapy [47]. It also emphasizes the possibility of using bacteriophages as vectors in drug and gene delivery systems, including therapies targeted towards the brain tissue, gastrointestinal tract, and lung via systemic or local delivery [48][49][50][51]. Furthermore, it also provides a reasonable explanation of the mechanism of direct horizontal gene transfer (HGT) between phages and eukaryotes, discussed in a later section.…”
Section: Bacteriophages Can Penetrate and Disperse Within Amentioning
confidence: 99%
“…is observation provides valuable information on the pharmacokinetic aspects of bacteriophage treatment, which is vital in the context of using bacteriophages as an alternative antimicrobial therapy [47]. It also emphasizes the possibility of using bacteriophages as vectors in drug and gene delivery systems, including therapies targeted towards the brain tissue, gastrointestinal tract, and lung via systemic or local delivery [48][49][50][51]. Furthermore, it also provides a reasonable explanation of the mechanism of direct horizontal gene transfer (HGT) between phages and eukaryotes, discussed in a later section.…”
Section: Bacteriophages Can Penetrate and Disperse Within Amentioning
confidence: 99%
“…Use of engineered phages to broaden the host range [137], conversion from lysogenic phages to lytic forms [138,139], expressing cell-penetrating peptides [95] and incorporate enzybiotics such as endolysins [140] and phage encoded cell wall degrading enzymes into their genomes have been shown to be effective in vitro, which have paved a way for future opportunities . For instance, Xu et al reported enhanced internalization of T7 phage by mammalian cells when human immunodeficiency virus type 1 TAT peptide was present on its surface [141]. The authors reported 2-log orders higher uptake of modified phage in mammalian cells (kidney epithelial cells) compared to T7 not modified with TAT peptide [141].…”
Section: Cinquerrui Et Al Proposed a Microfluidics-based Nano-encapsulation Of Phages Inmentioning
confidence: 99%
“…For instance, Xu et al reported enhanced internalization of T7 phage by mammalian cells when human immunodeficiency virus type 1 TAT peptide was present on its surface [141]. The authors reported 2-log orders higher uptake of modified phage in mammalian cells (kidney epithelial cells) compared to T7 not modified with TAT peptide [141]. In another instance, increased internalization of engineered M13 was reported by HeLa cells [142].…”
Section: Cinquerrui Et Al Proposed a Microfluidics-based Nano-encapsulation Of Phages Inmentioning
confidence: 99%
“…Modifying the genes of T7 phage can inactivate the bacteria‐resistant genes. [ 20 , 21 , 22 ] So far, there has not been a review dedicated to the theranostic applications of T7 phage.…”
Section: Introductionmentioning
confidence: 99%